AI and Integration of Islamic Values In Indonesian Journalism: A Study on @tvOneai and @metrotvnews - Nurfadhilah, Laila; Hero, Eko; Astini, Bunga (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
Artificial Intelligence (AI)'s emergence has revolutionized Indonesia's local and national journalistic media landscape. It brings new challenges in terms of information integrity. This research explores the opportunities and challenges local media in Indonesia face in integrating Islamic values through journalistic activities in media using AI technology. Through a qualitative approach of media content analysis, this study has analyzed the content of news broadcasts on the YouTube channels @tvoneai and @metrotvnews. A total of 124 videos were analyzed, consisting of 41 videos from @tvoneai and 83 short videos from @metrotvnews published from July 16 to July 29, 2024. Referring to the results of the analysis based on the concepts built, the researcher concludes that AI-based digital journalism activities in Indonesia have not maximally fulfilled the elements of Islamic values. It is reflected in some news reports in politics, social issues, economy, entertainment, and technology, which still lack consistency (Al-Istiqamah ), truth & accuracy (As-Shidiq), Amar ma’ruf Nahi Mungkar, justice & impartiality (Al-Musawah), humanity (Ta’awun), and reconfirmation (Tabayyun).